The accretion histories of brightest cluster galaxies from their stellar population gradients. Issue 4 (9th April 2015) - Oliva-Altamirano, Paola; Brough, Sarah; Jimmy,; Tran, Kim-Vy; Couch, Warrick J.; McDermid, Richard M.; Lidman, Chris; von der Linden, Anja; Sharp, Rob
Abstract : We analyse the spatially resolved stellar populations of nine local ( z < 0.1) Brightest Cluster Galaxies (BCGs) observed with VIMOS in Integral Field Unit mode. Our sample is composed of seven slow-rotating and two fast-rotating BCGs. We do not find a connection between stellar kinematics and stellar populations in this small sample. The BCGs have shallow metallicity gradients (median Δ[Fe/H] = −0.11 ± 0.1), high central metallicities (median [Fe/H][α/Fe] = 0 = 0.13 ± 0.07), and a wide range of central ages (from 5 to 15 Gyr). We propose that the reason for this is diverse evolutionary paths in BCGs. 67 per cent of the sample (6/9) show ∼7 Gyr old central ages, which reflects an active accretion history, and 33 per cent of the sample (3/9) have central ages older than 11 Gyr, which suggest no star formation since z = 2. The BCGs show similar central stellar populations and stellar population gradients to early-type galaxies of similar mass ( M dyn > 10 11.3 M⊙ ) from the ATLAS 3D survey (median [ Z /H] = 0.04 ± 0.07, Δ[ Z /H] = −0.19 ± 0.1). However, massive early-type galaxies from ATLAS 3D have consistently old ages (median Age = 12.0 ± 3.8 Gyr). We also analyse the close massive companion galaxies of two of the BCGs. These galaxies have similar stellar populations to their respective BCGs.